Derivation of human differential photoreceptor cells from adult human dermal fibroblasts by defined combinations of CRX, RAX, OTX2 and NEUROD. (24th January 2014) - Seko, Yuko; Azuma, Noriyuki; Ishii, Toshiyuki; Komuta, Yukari; Miyamoto, Kiyoko; Miyagawa, Yoshitaka; Kaneda, Makoto; Umezawa, Akihiro
<x xml:space="preserve">Abstract</x> Redirecting differentiation of somatic cells by over‐expression of transcription factors is a promising approach for regenerative medicine, elucidation of pathogenesis and development of new therapies. We have previously defined a transcription factor combination, that is, CRX, RAX and NEUROD, that can generate photosensitive photoreceptor cells from human iris cells. Here, we show that human dermal fibroblasts are differentiated to photoreceptor cells by the same transcription factor combination as human iris cells. Transduction of a combination of the CRX, RAX and NEUROD genes up‐regulated expression of the photoreceptor‐specific genes, recoverin, blue opsin and PDE6C, in all three strains of human dermal fibroblasts that were tested. Additional OTX2 gene transduction increased up‐regulation of the photoreceptor‐specific genes blue opsin, recoverin, S‐antigen, CNGB3 and PDE6C. Global gene expression data by microarray analysis further showed that photoreceptor‐related functional genes were significantly increased in induced photoreceptor cells. Functional analysis, that is, patch‐clamp recordings, clearly revealed that induced photoreceptor cells from fibroblasts responded to light. Both the NRL gene and the NR2E3 gene were endogenously up‐regulated in induced photoreceptor cells, implying that exogenous CRX, RAX, OTX2 and NEUROD, but not NRL, are sufficient to generate rod photoreceptor cells.